Study of various types of membranes for vanadium redox flow battery application - Lee, Jia Wei (2019)
The increase in renewable energy penetration to grids and micro-grids resulted in increase in use of battery storage. Today, the energy supplied from solar PV and battery has become cheaper than conventional electricity in many countries. Redox flow batteries are popular mainly due to their independent power and energy capacity sizing, among which the all vanadium redox flow battery (VRFB) is one of the mature and commercially available technology. VRFBs uses vanadium ions mixed in sulfuric acid as electrolytes in both tanks to store and generate the electricity. This is made possible due to Vanadium’s ability to exist in four oxidation states. VRFBs have numerous advantages, such as long life, stable capacity over the lifetime, low maintenance, flexibility of increasing the energy capacity just by increasing the size of the electrolyte storage tanks [1].